Knowledge management philosophy : communication as a strategic asset in knowledge management - Johannessen, Jon-Arild (Emerald points., 2020)
Knowledge Management is an important part of all business, and yet the discipline lacks a philosophy based on systemic thinking. Exploring this gap, expert author Jon-Arild Johannessen continues his research on knowledge management with the groundwork for a new philosophy. Across the four chapters in this book, Johannessen tackles the issues that have stopped a cohesive philosophy from being formed. Tackling the large questions first, he asks: what constitutes a philosophy for knowledge management? What quality criteria are relevant in a knowledge management philosophy? Johannessen also looks at how the emergence of the fourth industrial revolution has eroded and atomized the cohesion of social systems, and explores how knowledge management works in social systems, as well as whether social laws can be used to explain knowledge management systems. For students and researchers of information and knowledge management, Johannessen offers a new perspective on our current philosophies, bringing systemic thinking to the front of knowledge management philosophy.